Family Firms and Closed Companies in Germany and Spain - Fleischer, Holger; Recalde, Andrés; Gerald Spindler (Mohr Siebeck, 2023)
Family firms and closed companies are the most widespread form of business organization in Germany and Spain. As a field of comparative research, however, they have long been neglected. This volume puts them in the legal limelight. Eleven contributions explore typical legal problems with which courts, legal scholars and practitioners struggle in this area. These include majority/minority conflicts over retention of profits, executive compensation and other related party transactions. Particular attention is also paid to shareholder agreements which often contain a second layer of regulation in addition to the articles of association.